Rapid sizing of a hydrogen-battery storage for an offshore wind farm using convex programming - Ma, Zetao; Tian, Tian; Cui, Qiong; Shu, Jie; Zhao, Jianguang; Wang, Hao (International journal of hydrogen energy, 2023)
This paper carries out a comprehensive analysis on an offshore wind farm equipped with a hybrid storage comprised of hydrogen and battery, from the perspective of economic effectiveness. To rapidly evaluate the system economy, a computationally efficient convex program that takes the nonlinear storage efficiencies into account is provided, which can simultaneously and synergistically optimize the storage sizing and energy management over a long offshore wind cycle. In the analysis, a case study on the optimal configuration and operation of the hybrid storage is thoroughly investigated, answering what the scalings are and how the storage functions in the offshore wind farm. Comparisons to other offshore wind farms with none or only one storage type further demonstrate the advantage of combining hydrogen plant and battery. Influences of the offshore wind electricity price of grid parity and hydrogen price on the system economies, in the terms of total annual cost, net annual profit and hydrogen production cost, are also discussed, revealing sensitivity and dependency of the scalings. Finally, this paper presents the future potential of applying hydrogen plant in the offshore wind farm, from the angles of hydrogen production cost and energy saving. •Nonlinear modeling of the offshore wind-hydrogen-battery system is presented.•Convex programming is applied to optimize the plant sizes and control of the OWHBS.•Comparative analysis on the economics of the OWHBS is provided.•Potential of the hybrid hydrogen-battery storage is assessed.